UJI AKTIVITAS REPELAN MINYAK ATSIRI DAUN KEMANGI (Ocimum basilicum (L.) f. Citratum Back) TERHADAP NYAMUK Aedes aegypti DALAM SEDIAAN LOTION DAN UJI SIFAT FISIK LOTION - Mimiek Murrukmihadi; Dias Anita Fajarini (Majalah Obat Tradisional, 2015)
Essential oils of basil leaves that have spesific aroma can be used as a mosquito repellent. Lotions are more practical, easy to apply, easy to pour, and more efficient so repellent made in dosage form of lotion. The purpose of this study was to determine the repellent activity of volatile oil of basil leaf (Ocimum basilicum (L.) f. Citratum Back) against Aedes aegypti in lotion. Basil leaves are air-dried, then distilled by water and steam distillation for ± 6 hours. Essential oils with some concentrations(15% v / v, 25% v / v, and 35% v / v in 95% ethanol)are formulated in lotion. Physical properties (homogeneity, viscosity, dispersive power, and adhesion power) and repellent activity of lotions are tested. The data obtained are analyzed using the Kolmogorov-Smirnov test analysis, 2-way ANOVA test, and Turkey HSD test. The repellent activity is analyzed using One-Way ANOVA and Turkey test in level of 95%. The results showed that lotions with increasedessential oil concentration (15% v / v, 25% v / v, 35% v / v in 95% ethanol) are homogeneous and easily poured. Lotion with that increased concentration of essential oils of basil leaves (15% v / v, 25% v / v, 35% v / v in 95% ethanol) showed repellent activity with time protection of 3522, 4611, and 5435 seconds.